CHALLENGES OF ELECTION ORGANIZERS IN THE POST - COVID-19 PANDEMIC ERA - Dr. Redyanto Sidi, SH, MH; Putro Sucy Rezky Mz (Jurnal Ilmiah Advokasi, 2024)
As a global health phenomenon in the modern era, the COVID-19 pandemic has had a profound impact on all aspects of human life. Its influence extends beyond social life to encompass economic and political dimensions. The political aspect, in particular, demands attention in the post-pandemic era, primarily due to political agendas that necessitate the concentration of people at a single point and time, as seen in General Elections (Pemilu).Referring to the health protocols during the pandemic, a large concentration of people at one location and at a specific time is highly counterproductive in preventing the spread of COVID-19. However, elections are a critical agenda that lays the foundation for long-term human development. Therefore, conducting elections in the post-pandemic period entails certain consequences that must be addressed by election organizers.This study aims to uncover new trends in human activities during the pandemic period. Subsequently, these new trends pose challenges that must be addressed by election organizers to ensure that the political agenda can be carried out without contributing to an increase in COVID-19 infection cases. This research is qualitative in nature, employing a descriptive approach. Data were collected through literature and mass media sources. The findings reveal new trends in the social life of the Indonesian community post-pandemic, such as a heightened interest in working from home (WFH), the prevalence of fake news (hoaxes), and an increased level of public criticality. These factors have implications for the challenges faced by election organizers, including the ability to build public trust, effective communication skills, preparedness of human resources, and mastery of technology.Keywords: Pandemic, Elections, Effective Communication, Technology Mastery, Human Resource Readiness